Learning Clean and Healthy Lifestyle in Early Childhood through Hand Hygiene Dance - Khafifah, Nisa; Haryanto, Sri; Farida, Nur (GENIUS: Indonesian Journal of Early Childhood Education, 2022)
This research is motivated by the occurrence of a pandemic so that children are less active and their understanding of clean and healthy living habits, especially in washing hands, has not been carried out properly. In this study using a qualitative research approach where the type of research is descriptive qualitative. The purpose of this study was to find out how to inculcate clean and healthy living behavior through Hand Hygiene dance in TA Munajatul Khoir and find out teacher barriers in inculcating clean and healthy living behavior through learning Hand Hygiene dance in TA Munajatul Khoir. Data collection techniques used interview observation techniques. depth and documentation. The research subjects to be studied are parties in TA Munajatul Khoir, Kretek District, who have competence with this research, including school principals, teachers, staff and students at TA Munajatul Khoir kertek. This research uses trigulation research steps so that the research can check everything by comparing it with various sources of understanding, methods, or theories. The results showed that there were several stages in instilling clean and healthy living behavior in TA Munajatul Khoir, as well as an increase in the practice of washing hands after the children did hand hygiene dance lessons.   Abstrak Penelitian ini dilatarbelakangi oleh terjadinya pandemi sehingga anak kurang aktif bergerak serta pemahaman anak terhadap kebiasaan hidup bersih dan sehat khususnya dalam mencuci tangan belum terlaksana dengan baik. Dalam penelitian ini menggunakan pendekatan penelitian kualitatif dimana jenis penelitiannya adalah deskriptif kualitatif. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana penanaman perilaku hidup bersih dan sehat melalui  tari Hand Hygiene di TA munajatul Khoir dan mengetahui hambatan guru dalam penanaman perilaku hidup bersih dan sehat Melalui pembelajaran tari Hand Hygiene di TA munajatul Khoir.Teknik pengumpulan data menggunakan teknik observasi wawancara mendalam dan dokumentasi. Subjek penelitian yang akan diteliti adalah pihak-pihak yang ada di TA Munajatul Khoir Kecamatan Kretek, yang memiliki kompetensi dengan penelitian tersebut, diantaranya adalah kepala sekolah, guru-guru, staf, dan siswa-siswa di TA munajatul Khoir kertek. Pada penelitian ini menggunakan langkah-langkah penelitian trigulasi sehingga penelitian dapat merechek semua dengan jalan membandingkan dengan berbagai sumber pemahaman metode, atau teori. Hasil penelitian menunjukkan bahwa ada beberapa tahap dalam meanamkan perilaku hidup bersih dan sehat di TA Munajatul Khoir, serta adanya peningkatan praktik mencuci tangan setelah anak- anak melakukan pembelajaran tari hand hygiene.